Physical activity and the risk of falls in community-dwelling elderly in Central Java in urban and rural areas - Maisaroh Maisaroh; Dwi Rosella Komalasari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: In the elderly, there is a deterioration in the physical structure of the muscles. This includes a decrease in muscle strength and contraction, entering old age, the risk of falling will increase due to additional risk factors. This study will examine the effect of physical activity on the risk of falls in the elderly.Purpose: To understand the differences and impact of physical activity on the risk of falls in the elderly population in Rural and Urban environments.Method: This study used a cross-sectional design. The research was conducted in Boyolali Regency, Central Java, which represents rural areas, and Gonilan as a representative of urban areas. The research was conducted in August 2023 involving 116 participants in each region.Results: The Mann-Whitney test results showed a p-value of 0.000 <0.05, while the Fisher's Exact test resulted in a p-value of 0.538>0.5. Regression test results showed that the coefficient of determination in urban areas was 0.063 and rural areas was 0.029.Conclusion: From the results, it is concluded that there is a difference in physical activity between rural and urban neighborhoods. However, there is no significant difference in the risk of falls in the elderly between urban and rural areas. Furthermore, it can be concluded that the physical activity variable has a 63% influence on the risk of falls in urban areas, while the rest is influenced by other factors in each region.